If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22 + -0.5Y = x Solving 22 + -0.5Y = x Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-22' to each side of the equation. 22 + -22 + -0.5Y = -22 + x Combine like terms: 22 + -22 = 0 0 + -0.5Y = -22 + x -0.5Y = -22 + x Divide each side by '-0.5'. Y = 44 + -2x Simplifying Y = 44 + -2x
| 33x+4x=6 | | x=22+-0.5y | | x=22+-.5y | | 18-5n=3 | | 5a=7+28 | | .6x-.2=.4+.2x | | -6x+7=-4x+3 | | y-14=-14 | | 13=7g-8 | | 13X=-25+64 | | 7100+0.02p= | | 9(x+3)+13=2+2 | | 7v+1=-4v+12 | | 3z=-1 | | 6+r=15 | | -8=x-13 | | 8+t=9 | | -z+19=9z+19 | | 4x+4=31x-4 | | 16-x=12 | | y-14=14 | | 15x+12=5x-4 | | 3e+4=25 | | 2y-2=6(4-2) | | 2m-3=11 | | -6g-4g=100 | | 126-3x=24x+21 | | 12/3=6/2(3)+3 | | 16t^2-34t+18=0 | | 6x+10x=32 | | x-2(1x+10)=12 | | -0.5y+0.2=0.75y-0.2 |